Peningkatan Pengetahuan dan Keterampilan Orang Tua dalam Deteksi Dini Masalah Kesgilut pada Anak Disabilitas: Improving Parents' Knowledge and Skills in Early Detection of Oral Health Problems among Children with Disabilities - Ningrum, Valendriyani; Bakar, Abu; Mahata, Intan Batura Endo; Mailiza, Fitria; Femilian, Afyla; Ananda, Ricki (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Oral health problems are more vulnerable in children with disabilities than children in general. One of the efforts to minimize these problems is to increase parents' awareness of the importance of maintaining effective oral health in children with disabilities. Therefore, it is necessary to increase the knowledge and skills of parents who have children with disabilities in the early detection of oral health problems so that severity does not occur. This community service program is in the form of socialization activities and early detection skills training conducted for 71 parents/caregivers on 20 September 2024 at the RSGMP Baiturrahmah Hall, Padang City. Pre and post-assessment of parents' knowledge and skills were conducted, out of 72 parents/caregivers only 39 parents/caregivers completed the pre and post-test. The results of the analysis of existing data showed a significant increase in both the knowledge and skills of parents in the early detection of oral health problems. This activity needs to be carried out regularly as a promotional effort to improve the degree of oral health in children with disabilities.